Brand Loyalty on Online Taxi in Jakarta - Rahayu Rahayu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The performance of online taxi that is considered not good and online taxi drivers are trying to improve it. Through the determined hypothesis, the researchers would like to analyze the influence of word of mouth variable, service quality, and brand as the dependent variables towards customer loyalty as dependent variable or in form of hypothesis. The hypotheses are (1) What the impact of word by mouth variable to loyalty variable is, (2) What the impact of service quality to loyalty variable is, and (3) What the impact of brand variable to loyalty variable. The customers of online taxi keeps increasing; however, there are negative impressions from the customers in using online taxi because of the negative word by mouth, bad service, drivers and taxi without identity because the cars are private-owned car that is used for online taxi. The study uses verificative and descriptive research methods, while the data collection uses survey method with samples of 217 customers of online taxi in Jakarta, Indonesia in 2019- 2020. Sampling technique used is purpose sampling. The analysis tools used toward the variables uses average analysis and to respond the hypothesis, the analysis tool used is Structural Equation Model by using software lisrel. Descriptive analysis tool from some respondents answered positive and some answered negative. The SEM analysis tools for responding the hypothesis test are (1) Word of Mouth influences positively and significant to Customer Loyalty, (2) Service Quality influence positively and significant to Customer Loyalty and (3) Brand influences positively and significant to Customer Loyalty. Word of mouth influences significantly to loyalty for 0, 33. Service Quality influences significantly to loyalty for 0,41, and brand influences significantly for 0,54. Word of mouth, service quality and brand altogether imfluence loyalty for 79 %. Brand with the influence of 0,54 is the most dominant than word of mouth and service quality variable.